Guided “LegislEUlab” on the Drafting of Multilingual Legal Provisions in the EU: Concept of the Cologne Summer School for European Legal Linguistics - Dillmann, Ruben; Mattissen, Johanna (ZERL - Zeitschrift für Europäische Rechtslinguistik, 2021)
Legal training at German universities does not cover the practicalities and challenges of lawmaking. The innovative concept of the Cologne Summer School for European Legal Linguistics “LegislEUlab” encompasses the transdisciplinary teaching, simulation and analysis of the EU legislative procedure. The participants are students of law and translation from various EU Member States. In mixed teams, they prepare their own drafts, implementing the materials of a current proposal for an EU legislative act. They develop an awareness and deeper understanding of linguistic structure, multilingual drafting and its legal effects, comprehensibility of legal provisions and their interpretation and application. Die juristische Ausbildung an deutschen Universitäten vermittelt nicht Techniken und Herausforderungen der Rechtsetzung. Das innovative Konzept der Cologne Summer School der Europäischen Rechtslinguistik “LegislEUlab” umfasst die Lehre, Simulation und Analyse des EU-Gesetzgebungsverfahrens von einem transdisziplinären Ansatz aus. Die Teilnehmenden sind Studierende von Rechts- und Translationsstudiengängen aus verschiedenen EU-Mitgliedstaaten und arbeiten am Material eines aktuellen Vorschlags für einen Rechtsakt der EU in gemischten Teams eigene Entwürfe aus. Dabei entwickeln sie ein Bewusstsein und tieferes Verständnis für sprachliche Strukturen, die mehrsprachige Abfassung von Rechtsakten und deren Rechtswirkung, Verständlichkeit von Rechtsvorschriften sowie deren Auslegung und Anwendung. La formation juridique aux universités allemandes ne couvre pas les techniques et les défis que pose le processus législatif. Le concept innovant de la Cologne Summer School de Jurilinguistique Européenne « LegislEUlab » englobe l’enseignement, la simulation et l’analyse de la procédure législative de l’UE selon une approche transdisciplinaire. Les participants sont des étudiant(e)s en droit et en traduction de différents États membres qui, au sein d’équipes mixtes, élaborent leurs propres propositions basées sur les matériaux d’une proposition actuelle d’un acte juridique de l’UE. LegislEUlab vise à faire naître une prise de conscience et une compréhension plus approfondies des structures linguistiques, de la rédaction multilingue et de ses effets juridiques, ainsi que de la compréhensibilité des dispositions juridiques, de leur interprétation et de leur application.
Keywords: Europäische Rechtslinguistik; Rechtsetzung; Simulation; transdisziplinärer Ansatz; Rechtsetzungslabor; LegislEUlab; juristische Ausbildung; Übersetzung; 5. Europäisches Symposium zur Verständlichkeit von Rechtsvorschriften; European Legal Linguistics; Cologne Summer School; lawmaking; transdisciplinary approach; legal training; translation; Jurilinguistique européenne; législation; approche transdisciplinaire; traduction; formation en droit